Spectacular Bid : The Last Superhorse of the Twentieth Century - Lee, Peter (Book collections on Project MUSE., 2019)
A safety pin was all that kept Spectacular Bid from becoming the eleventh Thoroughbred to take the Triple Crown. This work examines Spectacular Bid from his humble beginnings -- he was born in a mud puddle on a horse farm in Versailles, Kentucky -- to his recognition as one of the greatest American racehorses. On the morning of the 1979 Belmont Stakes, Spectacular Bid stepped on a safety pin in his stall, injuring his foot. He had impressively won the first two races -- the Kentucky Derby and the Preakness -- but finished third in the Belmont, most likely due to his injury, making him one win shy of becoming the sport's third straight Triple Crown champion. But that loss did not prevent him from becoming one of horse racing's greatest competitors. After taking two months to recover, the battleship gray colt would go on to win 26 of 30 races during his career, with two second-place finishes and one third. He was voted the tenth greatest Thoroughbred of the twentieth century according to Blood-Horse magazine, and A Century of Champions places him ninth in the world and third among North American horses -- even ahead of the renowned Man o' War. This horse biography tells the story of the honest and not-so-glamorous colorful characters surrounding the champion -- including Bud Delp, the brash and cocky trainer who was distrustful of the Kentucky establishment, and Ron Franklin, the nineteen-year-old jockey who buckled under the stress and pressure associated with fame -- and how they witnessed firsthand the splendor and triumphs of Spectacular Bid. Including contemporary newspaper accounts of Bid's exploits and interviews with key players in his story, this is an encompassing look into the legacy of one of horse racing's true champions.